Effectiveness Of Online Transport Services: Service Attitude, Timeliness, And Price Appropriateness On Online Transport User Decisions In Medan City - Sianturi, Andry Sevchenko Gatuso; Sibarani, Hendra Jonathan; Theodora, Eka Martyna (Lembaga Riset Ilmiah, 2024)
Online transport services are one of the means of transport that has a level of comfort and safety that is in great demand today. Innovation in systems and services is one of the main attractions for application users to choose and use online transportation applications as a means of transportation that has affordability, service attitude and timeliness. In this study using quantitative methods, quantitative methods are research based on the philosophy of positivism, used to research on certain populations and samples. This study used 100 samples from Medan Labuhan District, using the cluster sampling method. The results of this study indicate that the service attitude variable has a t-statistics value of 6.249 > 1.66 and a p-value of 0.000, so service attitude has a positive and significant influence on decisions to use online transportation in Medan City. The timeliness variable has a t-statistics value of 0.784 < 1.66 and a p value of 0.433, so the timeliness does not have a positive and insignificant effect on the decision to use online transportation in Medan City, while the price appropriateness variable has a t-statistics value of 2.589 > 1.66 and a p value of 0.010, so the price suitability has a positive and significant effect on the decision to use online transportation in Medan City. With an Adjusted R. Square of 0.482 which can be interpreted that the variation in the online transportation usage decision variable can be explained by the service attitude variable, timeliness and price appropriateness by 48.2%, while the remaining 51.8% is explained by other variables outside of the variables studied